Enzyme assay and clinical assessment in subjects with a Chinese hotspot late-onset Fabry mutation (IVS4 + 919G→A) - Lin, Hsiang-Yu; Huang, Cheng-Hung; Yu, Hsiao-Chi; Chong, Kah-Wai; Hsu, Ju-Hui; Lee, Pi-Chang; Cheng, Kang-Hsiang; Chiang, Chuan-Chi; Ho, Huey-Jane; Lin, Shuan-Pei; Chen, Shih-Jen; Lin, Po-Kang; et al. (Journal of inherited metabolic disease, 2010)
Newborn screening for Fabry disease in Taiwan Chinese has revealed a high incidence of the late-onset GLA mutation IVS4 + 919G→A (∼1 in 1,500-1,600 males). We studied 94 adults with this mutation [22 men, 72 women; mean age: men 57.8 ± 6.0 (range 42-68), women 39.1 ± 14.1 years (range 19-82)]. Plasma α-galactosidase A activity assay was 10.4 ± 11.2% of normal in the men and 48.6 ± 19.5% of normal in the women. Echocardiography in 90 of the adults revealed left ventricular hypertrophy (LVH) in 19 (21%), including 14 of 21 men (67%) and 5 of 69 women (7%). Microalbuminuria, based on the urine albumin-to-creatinine ratio measured on at least two occasions, was present in 17 of 86 subjects (20%) (men: 5/20, 25%; women 12/66, 18%). At least one ocular manifestation consistent with Fabry disease was present in 41 of 52 subjects (79%) who underwent ophthalmologic examination, including 8 (15%) with conjunctival vessel tortuosity, 15 (29%) with cornea verticillata, 10 (19%) with Fabry cataract, and 34 (65%) with retinal vessel tortuosity. Among subjects over 40 years of age, men were more likely than women to have LVH [14/21 (67%) vs 5/25 (20%), p < 0.001]. Cardiovascular, renal and ocular abnormalities are highly prevalent in adult Taiwan Chinese subjects with the Fabry mutation IVS4 + 919G→A. Our findings contribute to the limited understanding of the course of this late-onset disease variant and underscore the need for close follow up in such patients.